Matematika untuk SMA/MA kelas X semester 1 - Miyanto; Suparno; Muklis; Nur Aksin; Arif Nursahid; Galih Wahyu Suseno; Sumartono; Jarot Raharjo (Intan Pariwara, 2019)
Buku ini merupakan kumpulan soal mata pelajaran Matematika untuk SMA/MA